Hubungan Mutu Pelayanan dengan Kepuasan Pasien Rawat Inap di Rumah Sakit Mandaya Karawang Tahun 2025 - Suntini, Nine; Kridawati, Atik; Aprillia, Yuna Trisuci (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2025)
Patient satisfaction depends on the quality of service provided. Service encompasses all efforts made by healthcare personnel to meet patient needs. A service is considered good if it meets patient expectations and is perceived as satisfactory rather than disappointing. Patient satisfaction is experienced from the moment of arrival until discharge from the hospital. This study aims to examine the relationship between service quality and inpatient satisfaction at Mandaya Hospital Karawang in 2025, as well as the influencing factors. This research is a quantitative study with a cross-sectional approach, analyzed using univariate, bivariate, and multivariate methods through ordinal logistic regression with 97 patient. The results show that the majority of inpatients (64.9%) felt satisfied with the inpatient services, while 35.1% were not satisfied. Bivariate analysis revealed a significant relationship between patient satisfaction and several services: registration, emergency department, room facilities, nursing, physician, pharmacy, nutrition, and security services. Multivariate analysis identified that the most dominant variables associated with patient satisfaction were registration service, emergency department service, and nutrition service. The odds ratio (OR) for nutrition service was 1154.820, indicating that good nutrition service increases the likelihood of inpatient satisfaction by approximately 1154 times. The Nagelkerke R Square value was 0.929, suggesting that the independent variables explain 92.9% of the variation in the dependent variable, leaving 7.1% explained by other factors.